Routledge handbook of sports journalism - Steen, Rob; Novick, Jed; Richards, Huw 1959- (Routledge international handbooks, 2021)
The Routledge Handbook of Sports Journalism is a comprehensive and in-depth survey of the fast moving and multifaceted world of sports journalism. Encompassing historical and contemporary analysis, and case studies exploring best practice as well as cutting edge themes and issues, the book also represents an impassioned defence of the skill and art of the trained journalist in an era of unmediated digital commentary. With contributions from leading sports media scholars and practising journalists, the book examines journalism across print, broadcast and digital media, exploring the everyday reality of working as a contemporary reporter, editor or sub-editor. It considers the organisations that shape output, from PR departments to press agencies, as well as the socio-political themes that influence both content and process, such as identity, race and gender. The book also includes interviews with, and biographies of, well-known journalists, as well as case studies looking at the way that some of the biggest names in world sport, from Lance Armstrong to Caster Semenya, have been reported. This is essential reading for all students, researchers and professionals working in sports journalism, sports broadcasting, sports marketing and management, or the sociology or history of sport.